BPD Empowerment Program in Optimizing Village Financial Implementation (Perspective Law No. 6 of 2014) - Maharani, Anggun Meinanda (Faculty of Law, Universitas Negeri Semarang, 2018)
Village government played an important role because it is considered as a basic element that directly interacts with the society and the policy or decision issued felt by the society directly. The issues studied were how is the BPD empowerment in optimizing village financial implementation as perspective Law No.6 of 2014? And how is the model of BPD empowerment in optimizing village financial implementation as perspective Law No.6 of 2014? The results showed that (1) BPD empowerment of Pringsari village is not optimal in conducting village finances related to activities in Pringsari village, (2) The model of BPD empowerment to the society has not been held optimally and still not transparent. The conclusion of the BPD empowerment in optimizing village financial implementation Pringsari village is not optimal yet. The model of BPD empowerment in Pringsari village that found is the achievement of APBDes planning process. Suggestion for the villager head and BPD in Pringsari village is realize the roles, jobs, functions and positions respectively.